2023
DOI: 10.1002/acr.25218
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy Study of the Pediatric‐Specific Ultrasound Scoring System for the Knee Joint in Children With Juvenile Idiopathic Arthritis

Patricia Vega‐Fernandez,
Kelly Rogers,
Alyssa Sproles
et al.

Abstract: ObjectiveTo validate the Pediatric Arthritis Ultrasound Scoring System for the knee joint (PAUSS‐knee) in children with juvenile idiopathic arthritis (JIA).MethodsChildren with JIA prospectively received a musculoskeletal ultrasound (MSUS) examination of the knee and a physical examination to determine presence/absence of clinical arthritis were enrolled in this study. MSUS images were scored using the PAUSS‐knee, a semiquantitative MSUS scoring system (0‐normal to 3‐severe) for B‐mode and Power Doppler‐mode. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“… 9 Vega-Fernandez et al found that ultrasound had a sensitivity of 0.83 for diagnosing synovitis in the knee joint when using contrast-enhanced MRI as reference. 23 The sensitivity demonstrated in this study may have many contributing explanations. The participants were referred to an MRI or whole-body MRI on clinical indication prior to inclusion.…”
Section: Discussionmentioning
confidence: 88%
“… 9 Vega-Fernandez et al found that ultrasound had a sensitivity of 0.83 for diagnosing synovitis in the knee joint when using contrast-enhanced MRI as reference. 23 The sensitivity demonstrated in this study may have many contributing explanations. The participants were referred to an MRI or whole-body MRI on clinical indication prior to inclusion.…”
Section: Discussionmentioning
confidence: 88%
“…The effectiveness and precision of clinical evaluations for examining entheses fall below acceptable standards, and imaging methods hold promise for their objective analysis [ 7 ]. One such technique is MSUS, which is safe and cost-effective [ 8 ]. In the assessment of enthesitis, ultrasound imaging can reveal a variety of abnormalities, including bursitis, formation of enthesophytes, disruption of the typical fibrillar structure, diminished echogenicity, swelling in the subcutaneous tissues, enlargement of the enthesis, and bone erosions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…When evaluated together with clinical assessment, synovial thickening, synovial effusion, and power Doppler (active synovitis) presence may support the diagnosis of juvenile idiopathic arthritis. Enthesis can be considered depending on the presence or absence of the entheseal changes of hypoechogenicity, thickening, enthesophyte, erosions, and Doppler signal at enthesis sites including achilles tendon, quadricipital tendon, and distal insertion of the patellar ligament [15,20,21]. To sum up, US provides high-resolution imaging of joints, tendons, ligaments, muscles and nerves in the pediatric population and has numerous applications in the broad field of Pediatric Rehabilitation Medicine.…”
mentioning
confidence: 99%